A novel bit based reversible image watermarking method - Tuncer, Türker; Özyurt, Fatih; Avci, Engin (Institute of Electrical and Electronics Engineers Inc., 2017)
Digital image watermarking methods are one of the mostly used methods for copyright protection and image content authentication. In this article, a new bit-based reversible digital image watermarking method (BB-RIW) is proposed for authentication in images. The proposed BB-RIW method consists of identifying the pixels to be stigmatized, generating the stamp, embedding the stamp, stamping, and image recovery. In the BB-RIW method, pixel bits belong to three groups: the most significant bits (MSBs), the middle bits (MBs) and the least significant bits (LSBs). In 8 bit images, 2 MSB, 4 OB and 2 LSB are used. Logical operations are performed on the MBs to check whether they are equal to 2 LSBs. If there is an equality, 2MSBs are embedded in 2LSBs of pixels. The positions of the matching pixels are recorded in the key. The key and mode 4 operator are used to stamp. In the image recovery phase, image recovery is performed using the key and MBs. Capacity and visual quality were used to assess the performance of the BB-RIW method. Experimental results show that the BB-RIW method can be used in many fields such as military and medical applications. © 2017 IEEE.
Bit Tabanli Tersinir Yeni bir Imge Damgalama Yöntemi
2nd International Conference on Computer Science and Engineering, UBMK 2017 -- 5 October 2017 through 8 October 2017 -- Antalya -- 132116
Keywords: Image authentication; Information security; Logic operators; Reversible image watermarking